Penerapan model picture and picture untuk meningkatkan hasil belajar matematika materi bangun datar pada siswa kelas IV SD Katolik 07 Xaverius Kairagi - Kuamba, Gebriani; Tamboto, Fabyana I.; Supit, Patricia H. (Educenter : Jurnal Ilmiah Pendidikan, 2022)
This study aims to improve the learning outcomes of mathematics about flat buildings by applying the picture and picture model in class IV students of Catholic Elementary School 07 Xaverius Manado. The approach of this research is classroom action research with the type of research model Kemmis and Mc. Tanggart model. The subjects in the study were 36 students. Data collection techniques are through tests, observations, interviews, and documentation. Data analysis used analysis of learning outcomes and the implementation of the picture and picture model. The results showed that: the application of the picture and picture model to improve math learning outcomes about flat buildings in grade IV students of Catholic Elementary School 07 Xaverius Manado has increased. The increase in student learning outcomes can be seen from the average pretest score of 58 with 3% completeness. In cycle I, the average value was 87 with 81% completeness. Cycle II average value 90 with 89% completeness. It can be concluded that there is an increase in math learning outcomes about flat shapes in grade IV students of Catholic Elementary School 07 Xaverius Manado.